Impact of Potassium and Nitrogen Fertilization on Bahiagrass Herbage Accumulation and Nutrient Concentration - Yarborough, J. K.; Vendramini, J. M. B.; Silveira, M. L.; Sollenberger, L. E.; Leon, R. G.; Sanchez, J. M. D.; Oliveira, F. C. Leite de; Kuhawara, F. A.; Gomes, V.; Cecato, U.; Soares Filho, C. V. [UNESP] (Amer Soc Agronomy, 2017)
Bahiagrass (Paspalum notatum Flugge) is the most utilized forage for beef cattle (Bos spp.) in Florida, but there is concern that bahiagrass pastures are declining due to insufficient K fertilization. Two studies determined the effects of K and N fertilization on bahiagrass herbage mass (HM) and nutritive value in field plots (Exp. 1), and greenhouse (Exp. 2). At two locations from May to December 2014 and 2015, Exp. 1 evaluated the combinations of three N fertilization levels (0, 50 kg N ha(-1) in May, or 50 kg N ha(-1) in May and August) and two levels of K fertilization (0 or 42 kg K ha(-1)). Potassium fertilization did not affect HM, crude protein (CP), or in vitro digestible organic matter (IVDOM); however, tissue K concentration increased from 10.6 to 11.2 g kg(-1) with increasing K fertilization. Plots fertilized with N had greater HM than the control, but there was no difference between plots fertilized in May only vs. those fertilized in May and August. Experiment 2 was conducted in a greenhouse in 2014 and 2015 with a factorial combination of three levels of N fertilization (0, 50, and 100 kg N ha(-1)) and four levels of K fertilization (0, 16, 33, and 66 kg K ha(-1)). There was a quadratic relationship between tissue K concentration and herbage accumulation (HA) and maximum HA occurred with tissue K concentration of 17 g kg(-1). Bahiagrass tissue K concentration and response to K fertilization are variable and can be related to fertilization levels.